MANAJEMEN LABA DITINJAU DARI SUDUT PANDANG PRAKTISI DAN AKADEMISI - Nafiah, Zumrotun (JURNAL STIE SEMARANG, 2013)
There is a difference views between practitioners and academics to earnings management. Differences due to differences in perspective view both sides of this managerial engineering activities. Practitioners assess earnings management as a problem that must be resolved for significantly affect company profits and decisions of stakeholders. Moreover, if the managerial engineering activity is carried out to mislead and harm others